Introduction to Electronic Document Management Systems in Small and Medium-Sized IT Projects - Wójtowicz, Radosław (Wprowadzenie do systemów zarządzania dokumentami elektronicznymi w małych i średnich projektach informatycznych, 2010)
The article presents chosen organizational and technical aspects of using electronic document management systems in IT projects which are small and medium-sized. Section 2 of the study concentrates on the key terminology. Section 3 describes the most important aspects of modelling and implementing of electronic document management systems.
Keywords: document management; electronic document; electronic document management system; project management; IT project